Perusahaan Healthcare dalam Bahaya: Pendekatan Analisis Risiko Keuangan Perusahaan - Vierkury Metyopandi; Ery Sulistyorini; Rafiq Firdaus Al-Asjim; Ulfa Miftachul Afifah (Syntax Idea)
Conditions after the pandemic subsides are another new challenge for healthcare sector companies in Indonesia. This research aims to investigate the influence of financial performance on company share prices in the healthcare sector. The company's financial performance, for all aspects of financial ratios, is often considered an important indicator for investors in making their investment decisions. Therefore, this research seeks to identify the influence between the financial performance of healthcare companies and their share price movements. This research method involves analyzing historical financial data of healthcare companies for the period 2019 to 2022, as well as their share price movements during the same period. The analytical tool used uses multiple linear regression analysis with the help of Eviews 10. The results of data analysis will be used to measure the extent to which financial performance influences stock prices. It is hoped that the results of this research will provide deeper insight for investors and stakeholders in understanding the factors that influence company share prices in the healthcare sector. This research concludes that return on equity and earnings per share have a significant influence on the share prices of health sector companies. These findings show that healthcare companies with high ROE and controlled debt ratios tend to have better stock performance. Apart from that, consistent EPS is also an important indicator in assessing a company's financial performance, which has a positive impact on investor confidence and share prices. This conclusion provides a holistic view of the close relationship between the financial aspects of healthcare companies and the stock market response to them. It is highly recommended for further research to use all financial ratio parameters to obtain comprehensive information regarding financial performance and stock prices.